(untitled) (Revista Lusófona de Educação, 2025)
Career Counseling is essential to improve personal development by defining competencies and linking them to the work environment. This discipline in the Spanish university context does not have the presence it should, even though it is the prelude to the working world. This aspect determines the need for techniques and strategies to promote it. This study responds to the need for Professional Orientation of university students through the program “My Professional Project”. Thirty-two students of the Pedagogy Degree participated in the experience with the objective of promoting competences in Professional Orientation to satisfy their needs prior to labor insertion. For this purpose, the usefulness and satisfaction of the program was designed and evaluated by means of a mixed study with quantitative predominance, through a questionnaire with a pre-posttest measurement, a satisfaction questionnaire and a semi-structured interview. The results show significant differences in a high percentage of the competencies evaluated and linked to the needs of the group, among which employability and decision making stand out. Concluding, the need to work on the professional project in university contexts is important in order to improve professional insertion.